(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The experiment was carried out Al- musaib orchand during the period 2015 - 2016 to find out the effect of three cuttings type (terminal, sub-terminal and basal)fig c.v wazeri, the second factor was studied the influence of method of planting (storage, without storage), third factor was studied for two times of cuttings (20/12/ 2015, 20/ 1/ 2016)..A factorial experiment within CRD with 3 Replications was adapted result could be summarized as follow : Treating fig with times cuttings in 20/12/2015 a gave a significant increase in rooting percentage and all vegetative growth parameters. The basal cuttings gave a significant effect on rooting percentage and most rooting and vegetative growth parameters. gave higher means of rooting percentage, Shoot length, Shoot girth, Shoot number, leaves number, leaf area vegetative dry weight and leaf content of chlorophyll. Method planting of cuttings without storage gave a significant increase of rooting percentage and all vegetative growth The interaction between cuttings type with method planting or with times cuttings treatment gave a significant effect for rooting percentage and most the vegetative growth parameters studied.The interaction between cuttings type, method of planting and times of cuttings gave the highest rooting percentage and values of most studied parameters.